The Relationship Between Hydrogen Peroxide, Zinc, and Humic Fulvic Acid in some of Elemental Content in Barley Plant (Hordeum vulgare L.) (Journal of the College of Basic Education, 2022)
The experiment was carried out with the aim of identifying the harmful effect of hydrogen peroxide (0,2,4)% and treating it with three increasing concentrations of humic fulvic acid (0,25,50) mg.L-1 and four concentrations of zinc (0,50,100,150) mg.L-1 in some of the major elements (nitrogen, phosphorus, potassium) and micro (zinc and iron) Randomized Complete Block Design with three replicates and 108 experimental units showed the following results:Hydrogen peroxide concentrations 4% have a negative effect on the values ​​of the studied traitsThe effect of both the humic fulvic acid and the zinc element had a positive effect on the content of the elements3 - The role of the high concentrations of each of them to give an increase rates for all those qualitiesThe triple interference between hydrogen peroxide concentrations 4% and spray with high concentration of acid and element was positive in reducing the impact of chemical stress. .